Evaluation of Cannula Safety in Injection of Poly-L-Lactic Acid - Nikolis A; Avelar LE; Enright KM (Dove Medical Press, 2021)
Andreas Nikolis,1,2 Luiz E Avelar,3,4 Kaitlyn M Enright2 1Division of Plastic Surgery, McGill University Health Center, Montreal, QC, Canada; 2Erevna Innovations Clinical Research Unit, Montreal, QC, Canada; 3Department of Forensic Anthropology, Civil Police Department, Minas Gerais, Brazil; 4Private Practice, Belo Horizonte, BrazilCorrespondence: Andreas NikolisErevna Innovations Clinical Research Unit, Montreal, QC, CanadaEmail anikolis@vicpark.comBackground and Objective: Poly-L-lactic acid (PLLA) has been used in various medical applications for decades, including aesthetic ones. The use of a cannula technique in injecting PLLA has been proposed in order to lower the incidence rate of adverse events (AEs) following treatment. Such AEs include nodule formation, which may occur less frequently by fanning the product with a cannula, thus creating a more uniform product placement compared to that resulting from the use of a needle. Currently, however, there is a lack of comparative research regarding the safety of cannulas versus needles for PLLA injections, as the selection of either remains highly subjective. Therefore, the objective of our study was to investigate the safety of cannula use in the administration of PLLA, in order to report safety outcomes.Materials and Methods: A single-center, retrospective chart review was conducted to examine the data of patients who had previously undergone treatment with PLLA in the form of Sculptra® Aesthetic™ in the face and/or neck regions. Twenty-seven subject charts met eligibility. Descriptive data regarding treatment and follow-up visits were collected and analyzed.Results: A total of seven AEs resulted from eighty-two treatment sessions (8.54%), with 6/27 patients having experienced at least one AE (22.22%). Mild bruising was the most commonly reported AE (57.14%). The majority of the AEs were mild and transient in nature, with one moderate AE being a nodule that was possibly related to a concomitant treatment. All AEs were resolved with follow-up care.Conclusion: Mild AEs such as bruising, swelling and pain should be expected following the use of a cannula for PLLA injections. However, the incidence rates of AEs following treatment can remain low if proper product preparation and treatment techniques are utilized.Keywords: poly-L-lactic acid, adverse events, cannula, injection techniques, antiaging